Touch Screen Tablets Touching Children's Lives - Joanne Tarasuik; Gabrielle Strouse; Jordy Kaufman (Frontiers Research Topics, 2018)
Touch screen tablets have greatly expanded the technology accessible to preschoolers, toddlers and even infants, given that they do not require the fine motor skills required for using traditional computers. Many parents and educators wish to make evidence-based decisions regarding young children's technology use, yet technological advancements continue to occur faster than researchers can keep up with. Accordingly, despite touch screen tablets entering society more than 5 years ago, we are in the infancy of research concerning interactive media and children. The topic has gained traction in the past couple of years. For example theoretical papers have discussed how interactive media activities differ from physical toys and passive media (Christakis, 2014), and how educational apps development should utilise the four "pillars" of learning (Hirsh-Pasek et al., 2015). Yet there has been little experimental research published on young children and touch screen use.